Maritime Vocabularies Learning In English For Children and Teenagers In The Geopark Area of The Bajo-Tilamuta Ethnic Village - Baga, Magdalena; Mahmud , Muzdalifah; Muhamad , Farid (International Journal Of Community Service, 2024)
Boalemo Regency selected the Bajo-Tilamuta Ethnic Village as a Cultural Diversity site for the Gorontalo Geopark due to the uniqueness of this ethnic group's way of life. The Bajo-Tilamuta tribe, one of the Bajo tribes, can be found on the coast of Gorontalo Province, specifically in Boalemo Regency. Despite residing on the coast, the Bajo-Tilamuta tribe remains isolated and distant from the broader population's settlements. However, the intensity of meetings between the Bajo and Gorontalo tribes often occurs through activities as fishermen and marriages between the Bajo and Gorontalo tribes. The Bajo tribe is known as a nomadic tribe at sea. Because of its spread beyond national borders, this tribe is known as a free border crosser. The Bajo tribe's reliance on the sea for shelter has led to their spread to various parts of the world, particularly in Southeast Asia. In the past, the Bajo tribe was known for exclusively living at sea, meaning they were born, lived, and died on boats. The Bajo people's way of life has now changed. Although the Bajo people still live on the sea's edge, their lives tend to settle in one place, leading many of their children to attend school and become graduates. The potential of the Bajo village as an ethnic geopark village hinges on the availability of human resources capable of supporting the village's designation as a geopark tourism village. Therefore, children and teenagers in the Bajo-Tilamuta Village require foreign language training, such as English. We take this action to prepare for the potential arrival of foreign tourists in the future. Through community service integrated with KKN (Community Service Program), students use the English teaching method for young learners by introducing maritime English vocabulary whose objects are in the daily lives of the Bajo Community, namely the sea and its environment.